Hyperphosphaturic Mesenchymal Tumor induced Osteomalacia– A Case Report - BB, Sharma; S, Sharma; A, Prasad; A, Ahuja; V, Kumar; S, Jilowa (Indian Journal of Case Reports, 2015)
Hyperphosphaturic Mesenchymal Tumor (HMT) is a very rare benign tumor of the soft tissue or bone which produces tumor induced osteomalacia, also called as oncogenic osteomalacia. This activity can only be stopped by the surgical removal of the tumor. We present a 23 years old man who presented with long standing bony pains without any relief by a variety of medications. The clue to the diagnosis was taken from pelvis skiagram, Magnetic Resonance Imaging (MRI) of the body, PET scan and the blood chemistry.